SOCIAL INEQUALITY AND ECONOMIC VULNERABILITY: A SOCIAL ECONOMIC PERSPECTIVE ON WELFARE POLICY - Nur, Muh; Ali, Azimah Haji; Anwar, Shamsul (Yayasan Adra Karima Hubbi, 2026)
Social inequality and economic vulnerability remain persistent challenges in contemporary societies despite the expansion of welfare policies and social protection systems. Economic growth has not been evenly distributed, leaving significant segments of the population exposed to income insecurity, precarious employment, and limited access to welfare benefits. This study aims to analyze social inequality and economic vulnerability through a social economic perspective that examines how welfare policy design interacts with labor market structures and social institutions. The research employs a qualitative research design combining policy document analysis, secondary socio-economic data review, and interpretive analysis of welfare policy implementation. The findings reveal that existing welfare policies tend to provide short-term relief while inadequately addressing the structural drivers of vulnerability, particularly informal employment, labor market flexibilization, and institutional exclusion. Economic vulnerability is shown to extend beyond officially defined poverty, affecting near-poor and precariously employed groups who remain insufficiently protected by current welfare frameworks. The study concludes that welfare policy effectiveness depends not only on resource allocation but also on institutional alignment with contemporary economic realities. A social economic approach is essential for understanding inequality as a dynamic and structural phenomenon, and for informing welfare reforms aimed at enhancing inclusivity, resilience, and long-term social protection.